Costa Rica – “Bogate Wybrzeże” = Costa Rica – „Rich Coast” - Napierala, Marek (Journal of Education, Health and Sport, 2016)
Napierała Marek. Costa Rica – “Bogate Wybrzeże” = Costa Rica – „Rich Coast”. Journal of Education, Health and Sport. 2016;6(2):111-121. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46249 http://ojs.ukw.edu.pl/index.php/johs/article/view/3392 https://pbn.nauka.gov.pl/works/715180 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2016. Revised 18.02.2016. Accepted: 18.02.2016. Costa Rica – “Bogate Wybrzeże” Costa Rica – „Rich Coast” Marek Napierała Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: turystyka, Kostaryka, parki narodowe. Key words: tourism, Costa Rica, national parks. Streszczenie Materiał stanowi dokument z obserwacji autora z pobytu w Kostaryce. Pobyt miał miejsce na przełomie 2015 i 2016 roku i był okazją do zwiedzenia miejsc ciekawych w klimacie podrównikowym. Podróżowanie to odwieczne ludzkie marzenie. Treścią wielu wyjazdów staje się odkrywanie nieznanego, szukanie odmienności w klimacie, florze i faunie, kulturze i zwyczajach ludzi. Można tu spotkać wiele gatunków zwierząt jak: małpy, krokodyle, liczne odmiany barwnych papug, kolibrów, tukany, ciekawe gatunki jaszczurek, węży, bogato ubarwione żaby, żółwie czy legwany. Ciekawe są także chrząszcze i wiele gatunków motyli. Kostaryka zostanie w pamięci miejscem fantastycznych krajobrazów, wakacyjny fenomenem. Abstract The material is a document from the observation of the author’s stay in Costa Rica. Visit took place at the turn of 2015 and 2016 years and was an opportunity to visit interesting places in equatorial climates. Travelling to the eternal human dream. The content of many trips becomes discovering the unknown, looking for differences in climate, flora and fauna, culture and customs of people. You can meet many animal species as .: monkeys, crocodiles, numerous varieties of colorful parrots, hummingbirds, toucans, interesting species of lizards, snakes, richly colored frogs, turtles and iguanas. Interesting are also many species of beetles and butterflies. Costa Rica is in the memory of the place fantastic landscapes, house phenomenon.